Management and Optimization of Hazards In Working Industries (International Journal of Scientific Research and Management (IJSRM), 2017)
:Industry isoneofthe oldest,anditisbeing realizedallover the worldthattheindustry has cometooccupy animportantposition inthe nationaldevelopmentprograms.Moreover, all overthe industry employsavery largeamountofmanpower.Still,very little attentionhasbeenpaid so fattothedevelopment ofindustry onscientificandorganized lines. Thereisnoworthwhile efforttousethe appropriate technologyin spite ofvastscope, variety, volume of the works, talent and resourcesin the developingcountries. The safety in Industry isone of the important measure to be takenbuthassomewhatbeenneglectedin the industry. Unfortunately to some extent, thishappensnotonly at themicrolevel buteven ona macrolevel. It must be accepted that the industryhastobeoperatedonscientificlines andithastocatertotheeconomicandsocial well-being ofallthoseinvolvedinit. Thestudy includeshow tointroducenew practicesforsafe guardof the workers fromtheworkplacehazardsintheindustry and optimizing hazards.